Bulletin des internationalen Bundes der Lithographen, Steindrucker und verwandten Berufe = . Bulletin of the International Federation of Lithographers, Printers and Similar Trades
No.1-74 text in Engl., French and German. - Since (1930) split into Engl.: (ZK 16035); French (ZK 16036), and German ed. (ZK 16034).